Perbanyakan Tanaman Nilam (Pogostemon cablin Benth.) Menggunakan Sistem Fotoautotrofik dengan Berbagai Konsentrasi Gula dan Jumlah Ventilasi - Inda Hidayati Rachmani; Arifah Rahayu; Sulassih (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2021)
Patchouli (Pogostemon cablin Benth.) is a plant that produces essential oils. In vitro propagation of Patchouli has been carried out as an effort to meet market demand. Photoautotrophic conditions with appropriate sugar concentration and number of ventilations is needed to get the best seedling growth. This research was conducted from June to September 2020 using a randomized complete block design with two factors. The first factor was sugar concentration (10, 20, and 30 g L-1) and the second factor was number of vents (0, 2, and 4 holes). The results showed that the interaction of sugar concentration and number of ventilation treatments affected to number of callus explants and number of leaves patchouli plant at 6 week after treatment. The best treatment for patchouli plant multiplication was 20 g L-1 of sugar without ventilation which increase number of leaves by 9-61% and number of nodes by 20% as compared to other treatments. Application of two holes ventilation increased number of roots by 10-20%, number and density of stomata 28-57% compared to other treatments. Increased number of roots, number and density of stomata in explants grown in photoautotrophic systems in vitro showed the ability to integrate environment and was thought to be more adapted to acclimatization for seedling production. Keywords: acclimatization, in vitro, photosynthesis, rooting, stomata